ARCILLAS COLOMBIANAS TIPO MONTMORILLONITA MODIFICADAS CON DODECIL-SULFATO DE SODIO PARA LA ADSORCIÓN DE CATIONES Ni2+ (2010)
The removal of dissolved nickel in aqueous solutions was studied by the use of montmorillonite clays, which combines a high specific area and elevated cationic exchange capacity, with a wider availability and economy compared to other materials such as exchange resins. In order to increase their affinity for Ni2+, the clay was modified with anionic surfactant, sodium dodecil sulphate (SDS). As a part of the characterization work, the mineralogical and chemical composition, and some physicochemical properties of the clay, were evaluated both in its natural and modified condition, showing the effectivity of the applied modification treatment. The adsorption tests showed an increase of about 40% in the Ni2+ adsorption capacity of the clay, when it was modified in 80 mM solution of SDS. The increase in the adsorbed amount of Ni2+ was proportional not only to the amount of modified clay but also to the concentration of SDS in the modifying solution Using this methodology , it was possible to achieve up to a 100% removal of nickel ions, using concentrations in the starting solutions of 80 ppm. In general, the results showed that montmorillonite clays, modified with anionic surfactant (SDS), represent an excellent alternative for the clean-up treatment of industrial effluents containing limited amounts of nickel ions.